Mutations in KIAA1109, CACNA1C, BSN, AKAP13, CELSR2, and HELZ2 Are Associated With the Prognosis in Endometrial Cancer - Qiao, Zhiwei; Jiang, Ying; Wang, Ling; Wang, Lei; Jiang, Jing; Zhang, Jingru (Frontiers in Genetics, 2019)
Endometrial cancer (EC) is one of the most common gynecologic malignancies. Emerging studies had demonstrated the mutations in genes could serve as diagnostic or prognostic markers for human cancers. In this study, we screened mutated genes in EC and found that the mutations in KIAA1109, CACNA1C, BSN, AKAP13, CELSR2, and HELZ2 were correlated to the overall survival time in patients with EC. Bioinformatics analysis showed KIAA1109 was involved in regulating NIK/NF-kappaB signaling, CACNA1C was found to regulate cell migration and proliferation, BSN was found to regulate Wnt signaling pathway, CELSR2 was involved in regulating cell-cell adhesion, nuclear import, and protein folding, and HELZ2 was found to regulate multiple immune related biological processes. The findings provided a novel therapeutic strategy in patients with EC.